(untitled) (REMUNOM, 2025)
The foraging behavior of Africanized honeybees (Apis mellifera) reflects the influence of environmental and seasonal factors, with the flow of entry and exit from hives constituting an important indicator of the external activity of worker bees. Understanding these variations throughout the day contributes to improving colony management and productivity. Accordingly, this study aimed to evaluate the entry and exit flow of Africanized honeybees in standard Langstroth hives. Weekly observations were conducted over one month in 32 colonies, during the periods from 10:00 to 11:00 a.m. and from 3:00 to 4:00 p.m., totaling 512 records (256 entries and 256 exits). The entry flow ranged from 15 to 1,117 bees (mean = 299.65; median = 251; SD = 203.7), whereas the exit flow ranged from 0 to 946 bees (mean = 150.37; median = 90; SD = 169.21). The data revealed that the entry flow was significantly higher than the exit flow (p < 0.05), with greater activity during the morning period, although no statistical difference was observed between the time intervals (p > 0.05). The correlation between temperature (21 °C to 25 °C) and flow was weak and not significant (entry: r = –0.05; exit: r = 0; p > 0.05). These results contribute to the understanding of the foraging behavior of Africanized honeybees and may support management strategies.